2009
DOI: 10.1115/1.3113683
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary and Posterior Scleral Mechanics—Part II: Experimental and Inverse Finite Element Characterization

Abstract: Background-The posterior sclera likely plays an important role in the development of glaucoma and accurate characterization of its mechanical properties is needed to understand its impact on the more delicate optic nerve head -the primary site of damage in the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
173
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(188 citation statements)
references
References 33 publications
15
173
0
Order By: Relevance
“…Different workers have made fundamentally varying assumptions about the mechanical behaviour of the cornea; Singh et al [16] assumed it to be anisotropic and linear elastic, whereas Pandolfi and Manganiello [17] assumed it to be both nonlinear and anisotropic. There is experimental evidence for nonlinear mechanical behaviour of both cornea and sclera [14] [17], though it has also been reported that nonlinear effects are not observed in the eye below IOP values of 4 kPa [6] [18]. Measurements show that the sclera is highly anisotropic [19] and this is consistent with the fibrous composite material model studied by Girard et al [18].…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Different workers have made fundamentally varying assumptions about the mechanical behaviour of the cornea; Singh et al [16] assumed it to be anisotropic and linear elastic, whereas Pandolfi and Manganiello [17] assumed it to be both nonlinear and anisotropic. There is experimental evidence for nonlinear mechanical behaviour of both cornea and sclera [14] [17], though it has also been reported that nonlinear effects are not observed in the eye below IOP values of 4 kPa [6] [18]. Measurements show that the sclera is highly anisotropic [19] and this is consistent with the fibrous composite material model studied by Girard et al [18].…”
Section: Introductionsupporting
confidence: 56%
“…Schulz et al [23] presented tensile results from human sclera and arrived at a modulus value 2.6 ± 2 MPa. Girard et al [18] have deduced modulus values for rhesus monkey sclera using a combined experimental and modelling approach, and found evidence of nonlinear behaviour, with stiffness increasing with IOP. They found the stiffness to be in the range 1.9 -3.5 MPa for an IOP of 10mm Hg, and 3.4 -4.7 MPa at 30 mmHg.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, to preserve vision, it is important to characterize two elements central to connective tissues, namely the orientation and organization of the collagen fibers that form them [5,6]. Several techniques have been developed for measuring collagen fiber orientation and organization, including small angle light scattering [7,8], x-ray scattering [9][10][11][12], non-linear microscopy [7,13,14] and magnetic resonance imaging [15,16], or for estimating them using inverse numerical methods [17,18]. The complexity of the eye calls for a technique that provides data at multiple scales, including high resolution (micron-scale) and broad field of view (several mm to cm) [19].…”
Section: Introductionmentioning
confidence: 99%